Detection of H. pylori Infection in Atherosclerotic Plaques of 180 Corpses in Referred to Forensic Medicine Center of Tehran in 2016-2017 - aber GHAREHDAGHI; Reza NASR; Jamil KHEIRVARI KHEZERLOO; Mohammad Reza AKBARI EIDGAHI; Mohsen TABASI; Mohammadreza GHASEMI; Elnaz MOZAFFARI; Reza AZIZIAN; Mohammad Reza ESKANDARION (Tehran University of Medical Sciences, 2018)
No Abstract####